Áreas de preservação permanente hídricas urbanas: conflitos técnicos e legais - Janducci, Millena Ariana Boueri (2020)
Urban water permanent preservation areas (PPAs) are protected by Brazilian Federal Law nº 12,651/2012 and have unquestionable relevance, acting against sediment carrying into watercourses, decreasing runoff, and preserving fauna and flora. Despite legal protection, these areas suffer from anthropic interventions. The general objective of this work was to describe and analyze the technical and legal aspects related to urban water PPAs at the Federal level since the misinterpretation of specific legislation can result in a series of negative consequences, especially the reduction of these spaces, the loss of its functionalities, and the increase of floods, which are ever more frequent in urban environments. This work also aims i) to present and analyze the restrictions for intervention in urban water PPAs at the federal level as a counterpoint to the regime regulated by the State of Minas Gerais; and ii) to identify their possible uses, in order to provide subsidies for decision making by those involved in the environmental licensing processes and, thus, preserve the PPAs and avoid their occupation by urbanized and urban expansion areas. The discussion was based on a broad bibliographic and documentary review that sought support in theses, dissertations, books and scientific articles, as well as on the digital platforms of the Federal Government and the State of Minas Gerais. The new Forest Code (Law nº 12,651/2012) was definitive regarding the application of the rules related to PPAs in the urban environment. However, it still requires improvement to remove the legal uncertainty that remains when it comes to urban areas. Such insecurity is supported by technical-scientific knowledge, or rather, its absence, given that this research indicated that the environmental function characteristics of urban water PPAs change with anthropic interference. This change may increase the effects of floods; favor opportunistic biota specimens and extinguish others by dumping effluents or by changing the course of watercourses; and bring risks or geological insecurity with civil construction works. Man's intervention is necessary, either to act in the environmental protection performed by water PPAs or to ensure the safety of the population that occupies these sensitive places, due to urban growth and expansion. We found that each water PPA site must have an occupation and protection plan ordered according to its technical characteristics. Therefore, public power can ensure the minimum environmental functions that must be contemplated in the master plan for the protection of the urban water PPAs. The role of municipalities to administer these areas, through the Master Plan, is of great concern since the standardization of environmental studies required for urban land regularization (Reurb) in PPAs can present certain flexibility of demand. In other words, it incurs the risk of loss of critical environmental functions of water PPAs, causing damage not only to the environment but also to humankind itself.